Parameter-optimized routing protocols for targeted broadcast messages in smart campus environments - Al-Sofy, Karam Mheide; Jalal, Jalal Khalid; Fadhil, Fajer F.; Mahmood, Basim (International Journal of Informatics and Communication Technology (IJ-ICT), 2025)
The spread of handheld mobile devices integrated with multiple sensors makes it easy for these devices to interact with each other. These interactions are useful in a variety of applications such as monitoring and notification systems that can be adopted in smart campuses. The performance of these applications depends primarily on the network infrastructure and network protocols. In cases of failure, smart campus requires the provision of effective alternatives that can handle essential services. Hence, this work uses the Wi-Fi mobile ad hoc network (MANET) as an alternative backup to the traditional infrastructure. The dynamic nature of such a network relies on individuals' mobility, this leads to a lack of end-to-end connectivity. To overcome this challenge, delay-tolerant networking (DTN) has been adopted as its primary approach to routing information inside campus. Spray and wait, binary spray and wait (BSW), and probabilistic flooding protocols are deeply assessed to ensure sustained communications in the working environment. The protocols’ parameters are comprehensively investigated and optimized. Moreover, the performance metrics that are used in the evaluation are messages consumption, node responsiveness, and coverage. The findings showed that the optimal protocol and its parameters is reliant upon the specific application and resources available.